Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3126/jonmc.v1i2.7304
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of mental retardation by gender, age, and age of diagnosis at Nobel Medical College, Biratnagar

Abstract: Abstract:Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Among the participants with ID in our study, the cases with mild ID types were more frequent, followed by moderate and severe ID types. These findings are similar to Koirala et al's study [ 27 ], in which also a high prevalence of mild ID was reported, followed by moderate, severe, and profound types. Further, the proportion of sensorineural defects was 19% and it constituted the second most prevalent category.…”
Section: Discussionsupporting
confidence: 92%
“…Among the participants with ID in our study, the cases with mild ID types were more frequent, followed by moderate and severe ID types. These findings are similar to Koirala et al's study [ 27 ], in which also a high prevalence of mild ID was reported, followed by moderate, severe, and profound types. Further, the proportion of sensorineural defects was 19% and it constituted the second most prevalent category.…”
Section: Discussionsupporting
confidence: 92%
“…It shows that compared to previous studies over there it was not only children who are brought to the hospital by their parents at an early age due to possible developmental delay or poor school performance but patients can reach health services at any age and for variety of reasons. 9 Unlike previous studies, there was no gender difference but it was predominantly urban and higher economic class dominated population. 9 Studies have consistently shown that individuals from low socioeconomic status and rural areas are over represented among those with mild mental retardation, but in this study differing finding could have been due to the profile of patient population visiting our hospital.…”
Section: Discussionmentioning
confidence: 56%
“…9 Unlike previous studies, there was no gender difference but it was predominantly urban and higher economic class dominated population. 9 Studies have consistently shown that individuals from low socioeconomic status and rural areas are over represented among those with mild mental retardation, but in this study differing finding could have been due to the profile of patient population visiting our hospital. 2,5,7,10 Majority of them consulted on their own with a specific health inquiry and expectation of treatment, though only some of them were referred by other specialists with a specific request of IQ assessment / diagnostic purpose (Psychiatrists & Gynecologists), and hardly by the school persons.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations